On the role of proprioception in making free throws in basketball - Sevrez, V.; Bourdin, C. (Research Quarterly for Exercise and Sport, 2015)
Purpose: The aim of this article was to investigate the role that proprioception of the upper limb plays in making basketball free throws. Method: We designed an experiment to directly correlate the performance of basketball players in a free-throw task and an elbow- and wrist-joint position sense task. Results: We found a moderately high correlation between the free-throw success rate and wrist-joint position sense and a moderate correlation between the free-throw success rate and elbow-joint position sense. In both cases, the most successful shooters also had the best proprioceptive results. Conclusions: The results indicate that free-throw success is, at least partly, determined by players' ability to sense the position of the distal joints of their throwing upper limb. From a motor-control point of view, this suggests that basketball players may organize the compensatory behavior between the joints of their free-throwing arm on the basis of proprioception. From a practical point of view, it points toward new training techniques to enhance free-throwing efficiency.